Teknologi Sebagai Bahan Peningkatan Kesadaran Ber-Pancasila Generasi Muda - Jeni Astari, Ni Putu; Sudarsana, I Ketut (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
The writing of this research aims to provide analysis in the form of descriptive analysis of the use of information technology to increase awareness of pancasila. The purpose of this study is to rebuild the nation's identity through moral education and pancasila education at a young age, especially in the technology and information sector. This research uses qualitative descriptive research methodology, which requires collecting factual and comprehensive data and identifying a problem through the collection of sources from previous research, including journals, books and from other references in the form of websites related to the following research. The results and conclusions of this study highlight the importance of pancasila in promoting optimism in society and preserving the identity of the archipelago in the face of advances in information technology. So that the government can prepare the golden generation while maintaining the national identity of the Indonesian nation.